A Research of Improving Data Fusing Algorithm Localization in Multistaic Sonar - Zhao, Jun Wei; Sun, Yong (Applied Mechanics and Materials, 2014)
For the purpose of improving the localization accuracy of bistatic sonar in baseline districts and side districts, the most effective method is to increase the number of transmitting and receiving stations, which forms a multistatic sonar system. The mature algorithm of multistatic sonar system which contains three distance measurements volume in one subset, calls the multistatic time-only localization (TOL) algorithm. This paper proposes a new algorithm which merges the TOL algorithm and IBOL algorithm. of improving the bearing-only localization algorithm. The simulation results show that the proposed localization algorithm exhibits higher accuracy compared with the TOL algorithm and IBOL algorithm. This new method can take full application of the measured information to improved the localization accuracy in the whole controlled area.